Faktor Risiko Kejadian Malaria di Wilayah Kerja Puskesmas Kenanga Kecamatan Sungailiat Kabupaten Bangka Propinsi Kepulauan Bangka Belitung - Harmendo, Harmendo; Wahyuningsih, Nur Endah; Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background: By the year 2007, Annual Malaria Incidence (AMI) was 38,51% in Bangka Belitung. In the working area of Kenanga Health Center, AMI was 23,42 per 1000 population and SPR was 25,90 percent. The aim of this study was to analyze the risk factors of malaria in the working area of Kenanga Health Center, Bangka Belitung. Method: It was an observational study using case control design. Samples were 152 respondents, with randomized cases were 76 people and controls were 76 people. Variables studied consist of environmental and behavioral factor. The collected data would be analyzed using Chi-square test and multiple logistic regression. Result: The result of this research indicated that the risk factors of malaria was characteristic of house wall with OR =5,11( 95% CI: 2,419-10,787), using of screen for ventilation with OR= 6,50 (95% CI: 3,197-13,215), condition of ceiling with OR= 4,72 (95% CI: 2,378- 9,371), water ponds around the house with OR= 3,128(95% CI: 1,611- 6,075), the habit of hanging out at night OR=4,69(95% CI: 2,369- 9,303), and the using of bed net with OR= 7,84 (95% CI: 3,427-17,969). Someone who had the habit of hanging out at night, sleep without using bed net, characteristic of wall of house, no ventilation screen, no ceiling, might have risk malaria incidence with probability 97 percent . Conclusion: The most dominant factor which influence malaria incidence in Bangka Belitung was using of bed net, using of screen for ventilation, characteristic of house wall, water ponds around the house and the habit of hanging out at nigh. Key words : malaria, risk factor, Bangka Belitung